Complete genome sequence of bacteriophage P26218 infecting Rhodoferax sp. strain IMCC26218 - Moon, Kira (Stand Genomic Sci, 2015)
Bacteriophage P26218 is a virus that thrives in freshwater and infects Rhodoferax sp. strain IMCC26218, both of which were isolated from Soyang Lake, Korea. The bacterial host, IMCC26218, belongs to the genus Rhodoferax and is closely related to R. saidenbachensis, with 98.7 % 16S rRNA gene sequence similarity. Bacteriophage P26218 has an icosahedral head structure with a diameter of ~52 nm and short tail of ~9 nm, which is a typical morphology of the Podoviridae family. Its complete dsDNA genome was 36,315 bp with 56.7 % G + C content. This is the first genome sequence reported for a lytic phage of the genus Rhodoferax. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40793-015-0090-1) contains supplementary material, which is available to authorized users.